The Influence of Sales Promotion, Product Quality and Customer Satisfaction on Customer Loyalty at PT. Salim Jaya Medan (A Case Study of Frozen Food Distribution) - Hengky Hengky; Marke Wijaya; Tri Wahyuni Wijaya; Irene Irene; Hendry Hendry (Budapest International Research and Critics University, 2020)
The object of this research was conducted at PT. Salim Jaya Medan, a company that is active as a distributor of frozen food, especially for raw materials for seafood and local and imported meat. In this company, the number of customers is decreasing from time to time. This is thought to be due to sales promotion factors, product quality and customer satisfaction. The research method used by researchers is quantitative, the type of research is descriptive. Primary and secondary data were used. The data collection technique is done by interview, questionnaire and documentation study. The data analysis used was multiple linear regressions, the coefficient of determination of simultaneous testing (F-test), and partial testing (t-test). The study population was 109 customers of PT. Salim Jaya Medan where 30 people were used as validity testing while the research sample was 86 people. The partial test results show that sales promotion, product quality and customer satisfaction have a positive effect on customer loyalty, while simultaneously it shows that sales promotion and customer satisfaction have a positive and significant effect on customer loyalty.